2007
DOI: 10.1111/j.1439-0396.2007.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Silybum marianum fruit extract in broiler chicken nutrition: influence on performance and meat quality

Abstract: The present study aimed at evaluating the effects of different doses of silymarin in diet on broiler performances and meat quality. For the trial, 180 male chicks (ROSS 508), were allocated in to three groups (S0, S40 and S80) of 60 animals each receiving a basal diet supplemented with 0 ppm, 40 ppm and 80 ppm of a sylimarin (provided by a dry extract of Silybum marianum fruits) respectively. During the trial feed consumption and live body weight were taken every 20 days. At the age of 40 and 60 days blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
45
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 35 publications
(41 reference statements)
8
45
2
Order By: Relevance
“…Meanwhile, the serum total antioxidant capacity (TAC) recorded significant higher values in all experimental groups compared to that level of control. At the same time, the present values of MDA for groups supplemented with (T) is opposite to the finding of Bolukbasi et al (2006) and Schiavone et al (2007) who considered thyme leaves and their contents of biphenylic as well as flavinoid compounds have been found to exhibit antioxidant capacity. As well as Rahim et al (2011) assured that thyme and oregano contain large amount of monotrepens thymol, carvacrol and flavinoids are exerting antioxidant properties.…”
Section: Effect Of Basil Thyme (Basil + Thyme) Zymogen Kemzyme (contrasting
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the serum total antioxidant capacity (TAC) recorded significant higher values in all experimental groups compared to that level of control. At the same time, the present values of MDA for groups supplemented with (T) is opposite to the finding of Bolukbasi et al (2006) and Schiavone et al (2007) who considered thyme leaves and their contents of biphenylic as well as flavinoid compounds have been found to exhibit antioxidant capacity. As well as Rahim et al (2011) assured that thyme and oregano contain large amount of monotrepens thymol, carvacrol and flavinoids are exerting antioxidant properties.…”
Section: Effect Of Basil Thyme (Basil + Thyme) Zymogen Kemzyme (contrasting
confidence: 99%
“…Moreover, the phenolic trepens improved stability of poultry production by decreasing lipid peroxidation. (Schiavone et al, 2007) suggested that high antioxidant activity of the thymol is due to the presence of phenolic hydroxy (OH) group that act as hydrogen donors to the proxy radicals which are produced during the first step of lipid oxidation which in turn retard the hydroxyl peroxide formation.…”
Section: Effect Of Basil Thyme (Basil + Thyme) Zymogen Kemzyme (mentioning
confidence: 99%
“…Nowadays, medicinal plants are receiving lots of attention as feed additives (Abdulkarimi et al, 2011;, especially as natural antioxidants. Silybum marianum fruit extract has been reported to reduce the lipid concentration of the thigh muscle and to increase the muscle's resistance to oxidative stress in broilers (Schiavone et al, 2007). Ciftci et al (2010) reported that hypocholesterolemic and antioxidant characteristics of cinnamon oil are related to better quality of meat.…”
Section: Introductionmentioning
confidence: 99%
“…1 Nutritional deficiencies or disturbances can depend on different factors and cause a variety of diseases. 2 Silybum marianum (family: Compositae) is an annual or biennial plant, native to the Mediterranean area and now it known to have spread to other warm and dry regions. 3 This plant also grows in many regions in Iran.…”
Section: Introductionmentioning
confidence: 99%